The Lithuanian Insurance Market Under Globalization Conditions - Lezgovko, Aleksandra (Ekonomika, 2003)
Surmounting the traditional capitalism, the capitalist private property and estrangement takes place by way of shifting from industrial economy to an economic system based on knowledge and information, formation of a new system of values of the modem man and transformation of a national state under the influence of processes of globalization of the economy and the society. The global economy and international financial markets arc the main indications of a forming new world order and a net-like boundless global informational society. One of the basic features of the informational economic system or informational economy of the end of the 20th - beginning of the 21st century is transformation of financial institutions into centers of national and international accounting and financial globalization. The positive and negative appraisals of financial globalization arc the emergence of a new configuration of the world economy: transfer from the regulated state system to the liberal model of money flow management. The main players on that financial market arc the global institutional investors in the new institutional forms of financial conglomerates uniting the banks, insurance. pension and investment (mutual, hedge, venture) funds as well as other companies of the financial environment - institutions distributing and re-distributing the financial resources of the world. The financial market of the world consist’ of an aggregate of financial and crediting organizations that play the role of mediators in re-distributing the financial assets of the world between the creditor and the debtor, the sellers and the buyers of financial resources. The world insurance market is a part of the financial market existing as an independent economic phenomenon and forming as an aggregate of national and regional markets, undergoing a number of changes under the influence of the globalization process. Globalization of the world insurance market expresses itself as a process of obliterating legal and economic barriers between national insurance economies caused by the changes in the world economy and aiming at forming a global insurance space. This phenomenon demonstrates itself in the following processes actively going on since the 90-ies of the 20th century: 1. Concentration and centralization processes reflecting in: • concentration of the world insurance and re-insurance capital which expresses itself in mass mergers, uptakes and absorptions, formation of strategic alliances of insurance and re-insurance companies on the global insurance market, as well as formation of traditional insurance companies on this has is; • wide-scale fusion of insurance, bank and crediting capital leading to formation of transnational financial groups; • concentration on the market of insurance mediators expressing itself in formation of huge international insurance brokerage companies by way of merging and buying up small and medium companies; • concentration of users of insurance services expressing itself in growing capitalization and changing their demand for traditional insurance services; 2. Modification of traditional forms and types of insurance services, development of new insurance products: • fusion of insurance and financial services and emergence of alternative insurance and re- insurance, securitization as a new way of organizing insurance coverage based on asset management of the insurers and the insurants; • changing demand fur “mass” insurance services, in particular activation of the insurers participation in pension insurance against the background of demographic aging of the population in countries of developed economy, crisis of the concept of the “welfare” state and reduced participation of the state in payment of old-age and disability pensions; • expansion of the sphere of usage of the private commercial insurance: insurance against political and military risks, insurance of credits and guaranties. insurance against informational risks. etc. 3. Change of market environment under conditions of: • full computerization of producers and users of insurance products and implementation of the Internet for sales/purchase of insurance and reinsurance services; • increasing devastation of insurance losses resulting from the development of urbanization, technical progress, cost increase of private and corporal property, influence of global climate changes; • expansion of access to foreign insurers and re-insurers on previously “closed” national markets of the countries of Central and Eastern Europe, Latin America and Asia; • universal liberalization of sales of insurance products caused by liberalization of state and supra-state regulation of financial and insurance markets. The process of globalization and convergence, alongside with opening wide access possibilities for separate countries to the financial resources of the world, contains in itself unforeseen risks related to weakening of regulation by the state and uncontrolled transfer of capital through state borders. Simultaneously with liberalization of state regulation, common universal “play rules” for the players of the global financial market arc being worked out, because “ ... one of the tasks for the 21st century is to find a way to combine some national sovereignty with financial unification ... ” [6, p. 29]. The latter facilitates conversion of national markets into constituting parts of the world market. A number of intergovernmental institutions and international financial organizations are engaged in working out and implementation of common standards and codes of behavior for all spheres of financial activities. also in the insurance sector. The financial globalization and formation of financial conglomerates of various organizational-institutional forms strengthens national, international and regional currency and financial instability. Therefore in scientific circles a question is regularly raised about the necessity of additional instruments for regulation on the world level.